g(-3)=4(-3)-3

Simple and best practice solution for g(-3)=4(-3)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g(-3)=4(-3)-3 equation:


Simplifying
g(-3) = 4(-3) + -3

Reorder the terms for easier multiplication:
-3g = 4(-3) + -3

Multiply 4 * -3
-3g = -12 + -3

Combine like terms: -12 + -3 = -15
-3g = -15

Solving
-3g = -15

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '-3'.
g = 5

Simplifying
g = 5

See similar equations:

| 3(3x-4)=(5x+2)+5 | | 9y+18=38 | | g(x)=4(-3)-3 | | 22x+100=70+25x | | 20x^2-5x+1=0 | | x^3+5x^2+8x-92=0 | | 3(3x+4)-8=9x+4 | | 3/7=n/.91 | | 4t-1=6 | | -15y+6x=30 | | 10n+10=180 | | y^4+4y^3-6y^2+4y+1=0 | | f(x+6)=6x-3 | | 6b+5=35 | | b-25=-1 | | 8z+7z-3z= | | 0.66x^2=24 | | 7Y=224 | | -5t^2+100t-425=0 | | 68-u=161 | | (5w-1)(2w-8)= | | 30+(-42)= | | -x+255=32 | | 30+y=-12 | | -7=23w+108 | | 66p=396 | | 9r=108 | | 72=204-x | | 15t=900 | | -13.1+(-2.6)= | | 5/9-7/9 | | 0.83*x=10 |

Equations solver categories